ASSESSMENT OF FINTECH PAYMENT PLATFORM SERVICE QUALITY IN SAVINGS AND LOANS COMPANIES IN ACCRA METROPOLIS (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The rapid adoption of FinTech payment platforms by Savings and Loans Companies in Ghana has transformed financial service delivery. Yet, little is known about whether these digital services meet customer expectations. While service quality assessments are common in banking, limited research has compared customers’ expectations and perceptions within the non-bank financial sector, creating a gap in understanding that is critical to enhancing user satisfaction and trust. This study addresses this gap by assessing the service quality of FinTech payment platforms in Savings and Loans Companies within the Accra Metropolis, Ghana, using the SERVQUAL model. The objective is to examine the gap between customers’ expectations and their actual perceptions of service performance across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A quantitative research design was employed, using a structured questionnaire administered to 386 customers. Paired samples t-tests revealed statistically significant negative service quality gaps across all five dimensions, indicating that customer perceptions fell short of expectations. The largest gap was observed in responsiveness, followed by assurance and reliability. Paired correlations showed moderate to strong positive relationships between expectations and perceptions, while Cohen’s d indicated small but practically meaningful effect sizes. The findings highlight critical shortfalls in the speed of customer support, system reliability, and trust-building features of FinTech payment platform services. Theoretically, the study extends the application of the SERVQUAL model to digital financial services in non-bank institutions. Practically, it offers diagnostic insights for service improvement, while policy-wise, it supports the development of digital service quality benchmarks and customer protection regulations in Ghana’s FinTech sector.